Design and Analysis of the Mechanism Realizing Trajectory and Gesture Claim - Ren Ziwen; Lin Song; Wang Gang (Jixie chuandong)
Based on the process requirement of a certain type packet machine,firstly,a new composite-mechanism based on gear- parallelogram mechanism is proposed,and the problem of singular point of structure is solved by composite- mechanism. Secondly,the problem of dynamic balance is solved by the structure designed. Then,the modal analysis and vibration test are carried out. The result of the time domain analysis and frequency domain analysis show that the vibration of new structure is more smaller than primary mechanism under the working condition of the 400 r / min. Under the working condition of 500 r / min,it has smooth movement,small vibration.